Rainfall Triggered Soil Slope Stabilized with Vetiver Plant - Kumar, Saurabh; Bahadur Roy, Lal (International Journal of Psychosocial Rehabilitation, 2024)
Rainfall has been identified as one of the main causes for slope failures in areas where highannual rainfall is experienced. Vetiver Plant root systems play a major role in the mechanicalproperties of soil by increasing soil strength and stability, and by increasing the porosity. Soilroot matrix bond the soil slope with the mechanical structure technique stabilization used tomitigate the slope failure. Investigation shows that the root framework causes a decrease ofwater penetration rate, reduce the rate of rising groundwater table, and expanding in soil shearquality. The root-reinforced soil is expected to be of higher strength as well as higherpermeability, which would help to reduce runoff by providing more infiltration, thus improvingthe slope stability. Vetiver root hedges interact with the soil to provide more shearing strength.Rainfall simulator has been designed in laboratory for the observation of the slope deformation,factor of safety, infiltration and seepage flow inside the slope. Numerical analysis of the slopestabilization with Vetiver Plant subjected to different rainfall intensity has been observed byMIDAS Engineering Software. During heavy rainfall Vetiver hedges are very effective toincrease the slope stability, maintain the matric suction and reduce the chances of slopeembankment failure.